Increasing burden of type 2 diabetes in Navajo youth: The SEARCH for diabetes in youth study. Issue 7 (15th July 2019) - Powell, Jeffrey; Isom, Scott; Divers, Jasmin; Bellatorre, Anna; Johnson, Melissa; Smiley, Janelia; Begay, Quanna; Benally, Christine; Hu, Diana; Saydah, Sharon; Pettitt, David J.; Pihoker, Catherine; et al.
Abstract: Aim: SEARCH has recently reported that both prevalence and incidence of youth onset type 2 diabetes (YT2D) increased among most US race/ethnic groups in the early 2000s. This study reports on the incidence (2002‐2013) and prevalence (2001, 2009) of YT2D in the Navajo Nation among youth age < 20 years from 2001 to 2013. Methods: SEARCH sought to identify prevalent YT2D cases in 2001 (N = 75) and 2009 (N = 70) and all incident YT2D cases in three periods: 2002 to 2005 (N = 53), 2006 to 2009 (N = 68), and 2010 2013 (N = 90) in Navajo Nation. Denominators were based on the active Indian Health Service user population for eligible health care facilities. Prevalence (per 100 000) and period‐specific incidence rates (per 100 000 person‐years) were computed for youth aged 10 to 19 years. Changes in prevalence were tested with a two‐sided skew‐corrected inverted score test, while changes in incidence were tested with Poisson regression. Results: YT2D prevalence was high but stable in 2001 and 2009, overall [146.6 (116.8, 184.0) vs 141.5 (112.0, 178.8), P = .65) and in all subgroups. In contrast, incidence rates increased particularly between the second and third periods overall and in most subgroups by age and by sex. Conclusions: These data confirm the high burden of YT2D among Navajo youth and suggest an increasing risk in more recent years. However, recent improvements in obesity reduction in this population demonstrate optimism for potential reductions in YT2D in Navajo Nation.